2011
DOI: 10.1097/fjc.0b013e3182239f36
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glutathione-depleting Drug Buthionine Sulfoximine and Aging on Activity of Endothelium-derived Relaxing and Contracting Factors in Carotid Artery of Sprague–Dawley Rats

Abstract: The role of the antioxidant glutathione (GSH) in mediating endothelial (dys)function, and how that role may depend on age, is unclear. The main purpose of the current study was to investigate the effect of 10-day treatment with the GSH-depleting drug l-buthionine sulfoximine (BSO) on endothelium-derived relaxing factor and endothelium-derived contracting factor activities in the isolated common carotid artery (CCA) of Adult and Aging animals. CCA blood pressure and flow were unaffected by age or BSO. Endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…This concurs with the earlier findings (Subramanian and James 2010), which indicated that the higher vulnerability of aged myocardium to peroxidative damage was mainly due to a decline in the level of free radical scavengers. Depletion of GSH results in enhanced lipid peroxidation, and excessive lipid peroxidation can cause increased GSH consumption during aging (Denniss et al 2011), as observed in the present study. GSH protects the cardiac cell membranes from the damaging action of lipid peroxide.…”
Section: Resultssupporting
confidence: 80%
“…This concurs with the earlier findings (Subramanian and James 2010), which indicated that the higher vulnerability of aged myocardium to peroxidative damage was mainly due to a decline in the level of free radical scavengers. Depletion of GSH results in enhanced lipid peroxidation, and excessive lipid peroxidation can cause increased GSH consumption during aging (Denniss et al 2011), as observed in the present study. GSH protects the cardiac cell membranes from the damaging action of lipid peroxide.…”
Section: Resultssupporting
confidence: 80%
“…2011). Briefly, AD CTL rats maintained a stable body weight throughout the treatment period, whereas the body weight in MA CTL rats was significantly decreased by 2.5 ± 0.5%, despite equivalent food and water intake.…”
Section: Resultsmentioning
confidence: 99%
“…2011). The declines in GSH:GSSG ratios (Liver: AD 31% and MA 25% vs. Diaphragm: AD 83% and MA 71%) and reductions in GSH content (Liver: AD 42% and MA 60% vs. Diaphragm: AD 96% and MA 95%), were more pronounced in the diaphragm than the liver, suggesting that BSO treatment may have increased ROS/RNS concentrations to an even greater extent in the diaphragm than the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As will be discussed, NOS can also act as a O2 generator. Antioxidant enzymes such as superoxide dismutase, glutathione, and catalase are also down-regulated or exhibit decreased activity with aging (Sun et al, 2004; Lund et al, 2009; Denniss et al, 2011; Fleenor et al, 2011). The final consequence is an unbalanced ROS production and NO depletion in detriment of the antioxidant capacity.…”
Section: No Generation In Cardiovascular Agingmentioning
confidence: 99%